2005
DOI: 10.1191/0748233705th232oa
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled vanadium pentoxide decrease gamma-tubulin of mouse testes at different exposure times

Abstract: Vanadium is an important environmental and industrial pollutant whose concentrations have increased in the last decades. Due to its status as reproductive toxicant and a microtubule damaging agent, the present study investigated by immunohistochemistry the effect of the inhalation of vanadium pentoxide on gamma-tubulin within somatic and testicular germ cells. Male mice inhaled vanadium pentoxide (V2O5) (0.02 M) 1 h/twice a week for 12 weeks. Our results demonstrated that vanadium accumulates in the testes sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
3
25
1
Order By: Relevance
“…1) which might be due to, an increase in the number of germ cells apoptosis, as a consequence of adverse effects on Sertoli cells and germ cell interaction. 28) In an another study MusaliGalante et al (2005) 29) reported that inhalation of vanadium pentaoxide in male mice lead to damage in spermatogenesis by decreasing the percentage of gamma tubulin in testicular cells which adversely affects the microtubules involved in cell division.…”
Section: Resultsmentioning
confidence: 99%
“…1) which might be due to, an increase in the number of germ cells apoptosis, as a consequence of adverse effects on Sertoli cells and germ cell interaction. 28) In an another study MusaliGalante et al (2005) 29) reported that inhalation of vanadium pentaoxide in male mice lead to damage in spermatogenesis by decreasing the percentage of gamma tubulin in testicular cells which adversely affects the microtubules involved in cell division.…”
Section: Resultsmentioning
confidence: 99%
“…(Badmaev et al 1999). Several commercial dietary supplements and multivitamins also contain vanadium in the range of 0.0004-12.5 mg. V is also widely used in the manufacturing of surgical implants, batteries, machinery, steel tools, in catalyst-based recycling processes, photographic developers, and semiconductors, oil refineries and power plants using vanadium-rich fuel oil and coal (Mussali-Galante et al 2005). However, there are no studies reporting its reproductive effects in humans, even if few studies investigated the reproductive toxicity of V into different experimental animals showing destructive spermatogenesis, necrosis of Sertoli cells, spermatocytes and spermatogonium, which is caused by chronic V ingestion and inhalation of vanadium pentoxide (Fortoul et al 2007).…”
Section: Vanadium (V)mentioning
confidence: 99%
“…Previously, our group and others reported the vanadium interaction with cytoskeletal proteins like tubulin, actin and intermediate filaments [17,18]. Cytoskeleton and nucleoskeleton are related, and remodeling of cytoskeleton intervenes in nuclear structure [19].…”
Section: Discussionmentioning
confidence: 99%